Assessing factors that influence young children's food preferences and choices. Issue 1 (30th October 2018) - Zonneveld, Kimberley L. M.; Neidert, Pamela L.; Dozier, Claudia L.; Gureghian, Danielle L.; Bayles, Makenzie W.
Abstract : Researchers have identified an unbalanced diet as a key risk factor in the etiology of many chronic diseases (World Health Organization, 2003 ). Although researchers have found that numerous factors influence children's food choices, no assessment exists to identify these factors. In Experiment 1, we established preliminary empirical evidence of children's preferences for healthier and less‐healthy foods, and found that 16 of 21 children preferred less‐healthy foods to healthier foods. In Experiment 2, we established the utility of an analogue, competing parameters assessment designed to approximate children's food choices in the natural environment. We identified either quality or immediacy as the most influential parameters governing four of four childrens' food choices. We found that effort influenced the efficacy of these reinforcer parameters in a predictable manner for one of four children.